Correlation between number of perforators of deep inferior epigastric artery perforator flap and its incidence of vascular complications in postmastectomy breast reconstruction - Fady Mohammad Alkonaiesy; Hisham Mahmoud Elminawi; Omar Shereef Omar; Tarek Ahmed Amer (Cairo : Fady Mohammad Alkonaiesy, 2016)
Breast cancer is the second most common cancer among women and the second leading cause of death secondary to cancer. Techniques that are used in treatment of this disease have evolved through the years to eradicate the tumor cells completely while restoring the patients' pre- disease state. The rate of post-mastectomy breast reconstruction doubled from 13% to 26% between 1998 and 2007 in United States due to multiple factors. The number of patients seeking reconstruction will continue to rise as patients become more aware of their options, and as reconstructive efforts continue to focus on increasing aesthetic outcomes with less donor site morbidity
Thesis (Ph.D.) - Cairo University - Faculty of Medicine - Department of General Surgery
Issued also as CD
Keywords: Breast cancer; Breast Reconstruction; Perforators of Deep Inferior